Transfer of ritual - Langer, Robert; Lüddeckens, Dorothea; Radde-Antweiler, Kerstin; Snoek, Joannes A. M. (Journal of ritual studies, 2006)
This paper investigates an aspect of the dynamics of ritual which is so far unresearched and hardly systematized: the phenomenon of 'transfer of ritual'. It attempts to bring order to the issues associated with this thorny problem, dividing them into two independent 'sets' (together also referred to as a 'matrix'), which can, in our opinion, be used as an analytical instrument. During the last three years, the possibilities for application of this instrument were tested and further enhanced.